2014
DOI: 10.1007/s12217-014-9367-z
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of a Thermocapillary-Buoyant Flow in a Liquid Bridge with Heat Transfer Through the Interface

Abstract: a b s t r a c tThe hydrodynamic stability of a thermocapillary flow in a finite-size liquid bridge, with a non-deformable interface, heated from above and surrounded by a passive gas is examined by means of three-dimensional direct numerical simulations. Convective flow in 1 cSt silicone oil with Pr ¼ 18 is driven by combined effects of buoyancy and thermocapillary forces. Effects of the interfacial heat exchange on hydrothermal stability of the bulk flow are evaluated for various external thermal conditions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…2014; Watanabe et al. 2014). Also, the possibility of imposing an external gas flow shows promise for a control of the onset of hydrothermal waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014; Watanabe et al. 2014). Also, the possibility of imposing an external gas flow shows promise for a control of the onset of hydrothermal waves.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Romanò & Kuhlmann (2019) has shown, however, that modelling the heat transfer across the interface by Newton's law tends to underestimate the thermocapillary driving, except very close to the cold rod. Motivated by the experimental evidence of the strong impact of the heat transfer across the interface (Kamotani et al 2003;Yano et al 2017), and with improved computing capabilities, more recent numerical approaches take into account the flow and heat transport in the surrounding gas phase (Shevtsova et al 2014;Watanabe et al 2014). Also, the possibility of imposing an external gas flow shows promise for a control of the onset of hydrothermal waves.…”
Section: Introductionmentioning
confidence: 99%
“…The first experiments controlling ambient conditions around a LB (Kamotani et al 2003;Mialdun & Shevtsova 2006;Irikura et al 2007;Watanabe et al 2014) indicated that heat exchange between the liquid and the ambient gas is an important factor that influences the instability mechanisms. However, in numerical studies, in order to optimize the computing time the problem is typically modelled as a single-phase liquid flow when the gas phase next to the LB is ignored, assuming that the viscosity and thermal conductivity of the gas are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…We will not supply further details on the experimental setup and procedure. The related information could be found in, e.g., Melnikov et al (2013a) and Watanabe et al (2014). Results of the data processing are shown in Section "Chaos Analysis of Experimental Data".…”
Section: Experimental Apparatus and Conditionsmentioning
confidence: 99%